280. MULTI-OMIC FEATURES OF OESOPHAGEAL ADENOCARCINOMA PATIENTS PRE-TREATED WITH PREOPERATIVE NEOADJUVANT THERAPY. (24th September 2022) - Naeini, Marjan; Newell, Felicity; Aoude, Lauren G; Bonazzi, Vanessa F; Patel, Kalpana; Lampe, Guy; Koufariotis, Lambros T; Lakis, Vanessa; Addala, Venkateswar; Kondrashova, Olga; Johnston, Rebecca L; Sharma, Sowmya; et al.
Abstract: The incidence of oesophageal adenocarcinoma (OAC) is rising in Western countries, with a 5-year overall survival (OS) rate of 14%. Curative treatment based on oesophagectomy is only suitable for ~50% of patients due to late-stage diagnosis. While the addition of preoperative chemotherapy or chemoradiotherapy has improved OS in OAC patients, little is known about the molecular basis of treatment response and patient outcomes. We investigated multi-omics data including whole-genome sequencing, RNA sequencing, methylation profiles and immunohistochemistry from 115 OAC patients mostly from DOCTOR phase II clinical trial that utilized neoadjuvant therapy (ANZCTR-ACTRN12609000665235). We identified genomic features associated with poor OS, such as the APOBEC mutational signature. We also showed that positron emission tomography non-responders have more sub-clonal genomic copy number alterations. RNA sequencing and methylation profiles suggested four immune clusters associated with OS and progression-free survival. The immune-suppressed cluster was associated with worse survival and epithelial-mesenchymal transition signature and enriched with myeloid-derived cells. The immune hot cluster was associated with better survival and enriched with T-cells, myeloid-derived cells, interferon-gamma and alpha responses, and immune markers such as CCL5, CD8A, and NKG7. We investigated multi-omic features of OAC tumours from patients who were part of phase II clinical trial. We discovered prognostic features such as mutational signatures and complex genomic events. We identified distinct immune clusters associated with patient outcomes and the potential of immunotherapy for select clusters. We characterized molecular features of OAC patients which has the potential to predict responses to neoadjuvant therapy and develop better-selected therapy, monotherapy, or combination therapy in the future.